The upgrading and downgrading of occupations : status redefinition vs. deskilling as alternative theories of change - DiPrete, Thomas A. [Verfasser] (My University, 1988)
"This paper criticizes the deskilling hypothesis for temporal change in occupations. Case studies of occupations alleged to support the deskilling hypothesis have typically been insensitive to the internal heterogeneity found within occupations, and to the fact that the boundary between adjacent occupations located on the same functional hierarchy can shift over time. When these factors are explicitly taken into account, it is found that apparently compelling evidence for the thesis of clerical downgrading better supports an alternative explanation, which might be called the process of status redefinition, an aspect of the process of professionalization. The case of clerical workers in the federal government is examined in some detail." (author's abstract) ((en)) Der Autor setzt sich kritisch mit der Dequalifzierungshypothese auseinander. Unter Bezug auf die Entwicklung der Angestellenqualifikationen in den Vereinigten Staaten seit dem 19. Jahrhundert spricht der Autor dagegen von einer Umdefinition des beruflichen Statusses. Er rückt dabei die interne Heterogenität von Beschäftigungen in den Vordergrund. Innerhalb der gleichen funktionalen Hierarchieebene können sich danach die Trennungslinien zu angrenzenden Angestelltentätigkeiten verschieben. (IAB)
Höher- und Niedrigereinstufung von Berufen
Keywords: G 2.3.4 Qualifikationswandel; G 1.2.3.2 Anforderungen & Bedarfe; T 1.2 Historische Berufsbildungsforschung; S 3.2 Unternehmen und Behörden; G 2.3.1 Arbeitsteilung & -organisation; Dequalifizierung; Qualifikationswandel; Historische Entwicklung; Angestellter; Öffentlicher Dienst; Betrieb; Hierarchie